Learning FL in Psycho-socio-religious Perspective - Darwis, Djamaluddin (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Language is one of the basic needs for human beings, because besides as personal being, human is social being as well. Human does not live alone in an isolated island, he lives in a community with many people from different ethnical and cultural background. The role of a language has been recognized significantly as tool for social communication and cooperation. The contact of many different people with varieties of background has been taking place for the past centuries. A lot of loaned words in a certain language is an evidence that there has been contact between two nations with different language background. There are many influential factors why people learn foreign language. This brief paper is trying to explore the background of learning foreign language. Among of the factors are psychological, social and religious. In term of psychology human has psychological potential to acquire language through learning. Learning is defined as psychological process to change the behavior.  There is close relationship between psychology of language and psychology of learning which includes attitude, motivation, intelligence, aptitude and other related factors. The other factor is social factor, language is part of social life, we are aware that there is a close relationship between language and society. We know that there is no language without society as language user, and there is no society without language as a means for communication. We cannot use a language for communication without   involving society, with whom   we are going to talk.  In learning foreign language it is not only learning linguistic skill but also communicative skill, how to use learned language in authentic communication.  There are many social reasons why people learn foreign language, among of the reasons are educational, commercial, political, cultural and the likes. The other factors of learning foreign language is religious purpose, either it is because of the teaching of the religion explicitly or implicitly orders to learn foreign language or because of religious obligation to spread religious belief to people all over the world. In Islam there are many verses in the Holy Quran that state the importance of learning language, foreign language and also human potentials in mastering language. The Holy Book also states the importance of human communication in order to work together to achieve social welfare. Learning foreign language (Arabic) also very important for ritual reason and for educational reason, because the Holy Book, the Word of God is written in Arabic language.